Spatial and temporal genetic diversity and population structure of hemileia vastatrix from peruvian coffee plantations - Quispe-Apaza C. (2021)
This research was supported by project N? 177-2015 FONDECYT (The National Fund for Scientific and Technological Development) and Universidad Nacional Agraria La Molina, Peru.